Science and Technology Resources: A Guide for Information Professionals and Researchers. - Peter Larsen (Issues in Science and Technology Librarianship)
The article reviews the book "Science and Technology Resources: A Guide for Information Professionals and Researchers," by James E. Bobick and G. Lynn Berard.